Inhibis Enzim α-Glukosidase dan α-Amilase dari Ekstrak Metanol Daun Buhu (Garuga floribunda Decne) Sebagai Antidiabetes - Nurvita Abdullah; Netty Ino Ischak; La Alio; Yuszda K. Salimi; La Ode Aman; Ahmad Kadir Kilo (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The Garuga floribunda (Garuga floribunda Decne) plant is one of the species known for its various medicinal properties. This research aims to investigate the inhibitory activity of α- glucosidase and α-amylase enzymes and to determine the optimum concentration of the methanol extract of Garuga floribunda leaves as an antidiabetic agent. The leaves extraction is obtained through an extraction process using methanol as the solvent and tested for itsinhibitory activity against the α-glucosidase enzyme using the p-nitrophenyl-α-D- glucopyranoside (p-NPG) substrate and the α-amylase enzyme using the DNS (3,5- dinitrosalicylic acid) substrate. The method is UV-Vis spectrophotometry. The Phytochemical tests of this plant reveal the presence of flavonoids, alkaloids, saponins, tannins, steroids, and terpenoids. The inhibition test results show that the methanol extract of Garuga floribundaleaves exhibited significant inhibitory activity against both enzymes. The highest inhibition percentage against the α-glucosidase enzyme is 91.09%, indicating very high antidiabetic activity. Meanwhile, the inhibition against the α-amylase enzyme is 7.56%, showing no significant antidiabetic activity. The optimum concentration for inhibiting both enzymes is 1000 ppm.